2021
DOI: 10.7189/jogh.11.04071
|View full text |Cite
|
Sign up to set email alerts
|

Global research priorities on COVID-19 for maternal, newborn, child and adolescent health

Abstract: Background This research prioritization aimed to identify major research gaps in maternal, newborn, child and adolescent health (MNCAH) to help mitigate the direct and indirect effects of the COVID-19 pandemic. Methods We adapted the Child Health and Nutrition Research Initiative methodology. We defined scope, domains, themes and scoring criteria. We approached diverse global experts via email to submit their research ideas in MNCAH and MNCAH-related cross-cutting/healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The COVID-19 pandemic has had a considerable psychosocial impact, particularly among the most vulnerable groups of the population, including women in pregnancy and in the first year after childbirth [ 1 , 2 ]. Therefore, the need for evidence focusing on the indirect effects of the COVID-19 pandemic on the health of women in the perinatal period, including psychosocial aspects, and on measures to improve access and provision of care, including psychosocial assistance, has been authoritatively affirmed [ 3 ]. In a time of such significant biological and psychosocial changes, women in pregnancy and the postnatal period have had to face stressful factors, such as fear of contagion and possible risks for the fetus or the newborn, social isolation, the impossibility of receiving emotional and practical support from family and friends, changes in the relationship with their partner exacerbated by forced cohabitation, the limitation of face-to-face medical and obstetrical consultations, anxiety of giving birth without the support of the companion of choice and economic uncertainty due to job loss [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has had a considerable psychosocial impact, particularly among the most vulnerable groups of the population, including women in pregnancy and in the first year after childbirth [ 1 , 2 ]. Therefore, the need for evidence focusing on the indirect effects of the COVID-19 pandemic on the health of women in the perinatal period, including psychosocial aspects, and on measures to improve access and provision of care, including psychosocial assistance, has been authoritatively affirmed [ 3 ]. In a time of such significant biological and psychosocial changes, women in pregnancy and the postnatal period have had to face stressful factors, such as fear of contagion and possible risks for the fetus or the newborn, social isolation, the impossibility of receiving emotional and practical support from family and friends, changes in the relationship with their partner exacerbated by forced cohabitation, the limitation of face-to-face medical and obstetrical consultations, anxiety of giving birth without the support of the companion of choice and economic uncertainty due to job loss [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research prioritisation exercises that have encompassed care for preterm or LBW infants have had various primary remits, including neonatal infections, 11 birth asphyxia, 12 newborn health, 13 , 14 maternal and perinatal health, 15 India, 16 humanitarian conflict settings, 17 and Covid-19. 18 We found one prior report from a decade ago (2012) on a research prioritisation exercise exclusively focused on preterm or LBW infants, particularly research for reduction of mortality. 19 The top ten research priorities identified then were predominantly health systems and policy research questions ( Table 3 ).…”
Section: Discussionmentioning
confidence: 97%
“…Most prior systematic research prioritisation exercises for newborn health have utilised the Child Health and Nutrition Research Initiative (CHNRI) methodology for setting priorities in health research investments, 9 , 10 and several of these efforts have identified RQs for preterm or LBW infants ( Table 3 ). 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 The CHNRI process engages topic experts to propose RQs, typically spanning the spectrum of epidemiological research, health policy and systems research, improvement of existing interventions, and development of new interventions. RQs are then assessed for answerability, effectiveness, deliverability, maximum potential for mortality reduction and the effect on equity.…”
Section: Discussionmentioning
confidence: 99%
“…Moynihan et al, 2021), and the World Health Organization calls for research to investigate how the pandemic influenced the provision of care in maternity facilities(Ahmed et al, 2021). Hence, our aim was to investigate the adherence to BFHI standards in Croatian maternity hospitals during the COVID-19 pandemic, and to compare the findings with those collected during the previous study…”
mentioning
confidence: 95%